Solution of Peak Junction Temperature with Crank-NicolsonÂ and SOR Approach - Aruchunan, E. (Springer Science and Business Media Deutschland GmbH, 2022)
The junction temperatures (JT) of many microelectronic devices have been reduced in order to improve device reliability and extend operating life. When the JT exceeds a certain threshold, electronic devices can suffer irreversible damage. As a result, a thermal control system can be used to achieve high performance in electronic systems. For predicting peak junction temperatures (PJT) of semiconductor devices, the heat conduction equation will be discretized using a numerical approach. In the first step, the heat conduction equation will be discretized using the Crank-Nicolson finite difference method. The Successive Over Relaxation (SOR) and GaussâSeidel (GS) methods will be used to solve the generated system of linear equations iteratively. The SOR method uses fewer iterations and takes less time to compute than the traditional GS iterative method, based on the results. In terms of PTJ accuracy, however, both methods are comparable. Â© 2022, The Author(s), under exclusive license to Springer Nature Switzerland AG.